Gender differentials in farm productivity: implications for household efficiency and agricultural policy - Alderman, Harold; Hoddinott, John F.; Haddad, Lawrence J.; Udry, Christopher R. (International Food Policy Research Institute, 1995)
Within many African households, agricultural production is simultaneously carried out on many plots controlled by different members of the household. Detailed plot-level agronomic data from Burkina Faso provides striking evidence of inefficiencies in the allocation of factors of production across the plots controlled by different members of the household. Production function estimates imply that the value of household output could be increased by 10 to 20 percent by reallocating currently-used factors of production across plots. This finding contradicts standard models of agricultural households. A richer model of behavior, which recognizes that the individuals who comprise a household compete as well as cooperate, has important implications for the structure of agricultural production and for the design of agricultural policy.